2009
DOI: 10.1038/aja.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in glutathione S-transferase T1 affect the surgical outcome of varicocelectomies in infertile patients

Abstract: Glutathione S-transferases (GSTs), superoxide dismutase 2 (SOD2) and NAD(P)H:quinone oxidoreductase 1 (NQO1) are anti-oxidant enzyme genes. Polymorphisms of GSTs, SOD2 and NQO1 have been reported to influence individual susceptibility to various diseases. In an earlier study, we obtained preliminary findings that a subset of glutathione S-transferase T1 (GSTT1)-wt patients with varicocele may exhibit good response to varicocelectomy. In this study, we extended the earlier study to determine the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Previous studies have suggested that the frequency of the GSTM1 null genotype is significantly higher in infertile men than that in fertile men (Tirumala et al, 2010) and that the decline in the semen quality of individuals with idiopathic infertility is associated with the GSTM1 / GSTT1 null genotypes (Finotti et al, 2009). Furthermore, the improvement in the semen parameters in response to varicocelectomy is significantly higher in patients with the GSTT1 present genotype (Ichioka et al, 2009), and the susceptibility of sperm and seminal plasma to oxidative stress is significantly greater in idiopathic infertile men with the GSTM1 null genotype than in idiopathic infertile men with the GSTM1 present genotype (Aydemir et al, 2007). The GSTM1 and GSTT1 present genotypes are related to a favorable response to varicocelectomy (Okubo et al, 2005), and the GSTM1 null genotype appears to predispose the sperm of patients with varicoceles to increased oxidative damage (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the frequency of the GSTM1 null genotype is significantly higher in infertile men than that in fertile men (Tirumala et al, 2010) and that the decline in the semen quality of individuals with idiopathic infertility is associated with the GSTM1 / GSTT1 null genotypes (Finotti et al, 2009). Furthermore, the improvement in the semen parameters in response to varicocelectomy is significantly higher in patients with the GSTT1 present genotype (Ichioka et al, 2009), and the susceptibility of sperm and seminal plasma to oxidative stress is significantly greater in idiopathic infertile men with the GSTM1 null genotype than in idiopathic infertile men with the GSTM1 present genotype (Aydemir et al, 2007). The GSTM1 and GSTT1 present genotypes are related to a favorable response to varicocelectomy (Okubo et al, 2005), and the GSTM1 null genotype appears to predispose the sperm of patients with varicoceles to increased oxidative damage (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2 Six case-control studies 1,3-7 were eligible concerning GSTM1 genotype (912 male infertility cases, 859 controls) and five casecontrol studies 1,4,6-8 were eligible concerning GSTT1 genotype (862 male infertility cases, 755 controls). All studies were conducted on Caucasian subjects except for one 6 in the case of GSTM1 polymorphism and two 6,8 in the case of GSTT1 polymorphism.…”
Section: N This Issue Of the Journal Of Humanmentioning
confidence: 99%
“…The characteristics of selected studies are summarized in Table 1. A total of 12 eligible studies met the inclusion criteria, including 11 studies for GSTM1 [14,15,[25][26][27][28][29][30][31][32][33] and 9 ones for GSTT1 [17,26,27,[29][30][31][32][33]. All the included studies were case-control studies.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%